Ù…Ù†Ù‡Ø¬ Ø§Ù„ØªØ±Ø¬ÙŠØ Ø¨Ø§Ù„Ø³Ù†Ø© ÙÙŠ ØªÙØ³ÙŠØ± Ø§Ø¨Ù† ÙƒØ«ÙŠØ±: Ø¯Ø±Ø§Ø³Ø© Ù„Ù†Ù…Ø§Ø°Ø¬ Ù…Ù† Ø§Ù„Ø¬Ø²Ø¡ Ø§Ù„Ø«Ù„Ø§Ø«ÙŠÙ† ÙÙŠ Ø§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ…: The method of Preponderance using Sunnah in Ibn kathir interpretation Study of verses of the juz' 30 of the Quran - MAHER BIN GHAZALI (Universitas Darussalam Gontor, 2023)
This research investigates Ibn Kathir’s interpretation of verses in the Juz’ 30 of the Qur’an for the purpose of revealing the method of Tarjih (Preponderance) using the Sunnah in the Ibn Kathir’s interpretation. The study tracks these verses that interpreted by Ibn Kathir and looks at his choices and Tarjih method of the interpretation. In order for the researcher to get acquainted with the method of Ibn Kathir in this matter, the study applies inductive method to examine the verses and collect related scientific studies and analytical method to analyze these verses and reveal the Tarjih methodology using the Sunnah. Thereby, it is apparent that the Tarjih method using Sunnah of Ibn Kathir counts on what was reported from the Prophet peace be upon him, the authentic Sunnah and the Hadith even if there is a weak point in the requirements that needs to be cleared or strengthened such as Shawahid (Witnesses) and Mutabaat (Follow-ups) or the meaning of Quranic context.